PERAN Lactobacillus bulgaricus DAN Streptococcus thermophillus DALAM PEMBUATAN YOGHURT CANGLO DENGAN PENAMBAHAN STROBERI (Fragaria x ananassa) - Siti Chalimah; Dewi Mayasari (Universitas Sebelas Maret, 2014)
Indonesia is rich in biodiversity , one of which various types of nuts that could potentially be a functional food products , one of which Tolo beans protein sources with high nutritional value (20-25 g/100g), B vitamins (thiamin , riboflavin , niacin , folic acid), minerals (Ca, Fe, P, K, Zn, Mg, etc ), and fiber . Not many products are developed into products Tolo beans yogurt . Yogurt is milk coagulation products produced through fermentation of lactic acid bacteria (Streptococcus thermophilus and bulgaricus Lactobaccilus). The purpose of the study, namely ,i) determine the effect of strawberry extract for quality improvement through organoleptic tests ,ii) determine the content of vitamin C and protein extracts with the addition of strawberryyogurt, iii ) optimizing the addition of strawberry extract to obtain optimum quality yogurt with a distinctive flavor of yogurt . The method used experiments with four perlakua , among others . without the addition , treatment of the second, third and fourth with the addition of strawberry extract 10, 20 and 30 cc/100cc canglo yogurt , with 2 kinds of bacterial inoculum of each 6 ml / treatment . The study design with completely randomized (CRD) of the factor is the addition of strawberry extract . Data were analyzed qualitatively (simple statistics) and quantitatively with Anova one lane . The results showed that the yogurt Canglo acceptable by the panelists . Yogurt canglo with the addition of strawberry extract preferred by panelists with a distinctive flavor and aroma , soft texture , but the most preferred in the treatment BA3 (extract strobery 30 cc) , because it has aroma , flavor , color , texture and acidity right , which indicated the quality organoleptiknya most good . Highest levels of vitamin C yaitu10 , 296 mg/100 cc yogurt , and protein content 4.84 % / 100 cc yogurt . Based on the research it can be concluded that the addition of strawberry extracts affect the quality canglo yogurt , protein, and levels of vitamin C. Suggestions for further research are expected to be more creative in choosing additional ingredients , so as to increase the levels of vitamin C and protein. Keywords : Tolo beans , yogurt Canglo , strawberries , vitamin C , protein